Closing in on the pathogenesis of the 5q- syndrome. Issue 5 (May 2010) - Post, Sean M; Quintáás-Cardama, Alfonso
Evaluation of: Barlow JL, Drynan LF, Hewett DR et al. A p53-dependent mechanism underlies macrocytic anemia in a mouse model of human 5q- syndrome. Nat. Med. 16(1), 59––66 (2010); and Starczynowski DT, Kuchenbauer F, Argiropoulos B et al. Identification of miR-145 and miR-146a as mediators of the 5q- syndrome phenotype. Nat. Med. 16(1), 49––58 (2009). Patients with 5q- syndrome are characterized by macrocytic anemia, normal to elevated platelet counts, and a propensity to develop acute myeloid leukemia. The 5q- syndrome is believed to be a clonal disorder of the hematopoietic precursors. Until recently, little was known regarding the molecular pathogenesis of this malignancy. Two recently published studies using genetic approaches have unraveled a small array of genes whose alteration recapitulates critical features of the 5q- syndrome including dysplasia, clonal dominance, and progression to acute myeloid leukemia.